Determination of Genetic Parameters and Inbreeding Depression of Half-Sib and Selfing Families to Developed as Baby Corn Variety - Nailan Nabila; Yudiwanti Wahyu; Winarso Drajad Widodo (Current Topics in Agricultural Sciences Vol. 6, 2022)
The objective of this study was to evaluated S_1 and HS families to be developed as baby corn variety. Baby corn is kind of vegetable that has high nutritional value and safe to be consumed fresh or in canned, but baby corn variety isn’t available in Indonesia. This study was conducted at Cikarawang experimental station, Bogor Agricultural University from May to December 2016, using eight open pollinated varieties as progenitor (\(S_°\)) and their inbreeding families (HS and \(S_1\) ). Significant differences were found among genotypes on baby corn traits. Mean of inbreeding families were lower than their \(S_°\) in baby corn traits except ear diameter. The best percentage of marketable baby corn was selfing families 37.56% . Inbreeding depression for \(S_1\) families were higher than HS families. The highest inbreeding depression was number of ear per plant, 20.25% for HS and 25.52% for \(S_1\) . The estimates of genetic effects (additive and dominance) for baby corn traits were specific in each \(S_1\) genotypes. In general, the gene action was predominantly additive for all traits in \(S_1\) families. Golden, Hawaii, Baruna, Lokal madura, and Mutiara selfing genotypes were advised to develop as open pollinated varieties, whereas selfing genotypes from Laksmi, Genjah melati, and Srikandi kuning were suggested to develop as hybrid varieties.